Competing in Organizations: Firm Heterogeneity and International Trade - Dalia Marin; Thierry Verdier (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2007)
This paper develops a theory which investigates how firms' choice of corporate organization is affecting firm performance and the nature of competition in international markets. We develop a model in which firms' organisational choices determine heterogeneity across firms in size and productivity in the same industry. We then incorporate these organisational choices in a Krugman cum Melitz and Ottaviano model of international trade. We show that the toughness of competition in a market depends on who - headquarters or middle managers - have power in firms. Furthermore, we propose two new margins of trade adjustments: the monitoring margin and the organizational margin. International trade may or may not lead to an increase in aggregate productivity of an industry depending on which of these margins dominate. Trade may trigger firms to opt for organizations which encourage the creation of new ideas and which are less well adapt to price and cost competition.
urn:nbn:de:bvb:19-epub-13345-5
Keywords: F12; F14; L22; D23; 330; international trade with endogenous firm organizations and endogenous toughness of competition; firm heterogeneity; power struggle in the firm